The expression of BHLHE22 in endometrial carcinoma: Associations with mismatch repair protein expression status, tumor-infiltrating immune cells, programmed death-ligand 1 and clinical outcomes - Lin-Yu Chen; Hsing-Yu Chen; Hung-Cheng Lai; Shiou-Fu Lin; Kuo-Chang Wen; Darmawi; Phui-Ly Liew (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Endometrial cancer (EC) shows substantial heterogeneity in their immune microenvironment. BHLHE22 is consistently hypermethylated in EC and high expression of BHLHE22 is likely to be immunosuppressive in the tumor microenvironment. Herein, we evaluated expression of BHLHE22, programmed cell death ligand-1 (PD-L1), CD8, CD68 and mismatch repair proteins in EC. Materials and methods: Immunohistochemistry on tissue microarray sections in primary EC to quantify BHLHE22, PD-L1, CD8 and CD68 was performed. The associations between the clinicopathological characteristics, mismatch repair status, and Kaplan–Meier analyses (including The Cancer Genome Atlas (TCGA) dataset) were analyzed. Results: Twenty-nine of 109 cases (26.6 %) had high BHLHE22 expression, which was associated with higher tumoral CD8, higher stromal CD68 and lower progesterone receptor (PR). Survival analysis of the TCGA dataset showed better overall survival in subgroups with high BHLHE22/high CD8, high BHLHE22/low M2 macrophage, and high BHLHE22/low myeloid-derived suppressor cell. The transcription start site region of BHLHE22 contained many predicted PR-binding elements. In EC cells, BHLHE22 expression increased with time after exposure to progesterone. Of the 115 ECs, 29 (25.2 %) had microsatellite instability. Mismatch repair-deficient ECs exhibited significantly more CD8-positive tumoral/stromal T lymphocytes and macrophages, and a higher percentage of PD-L1-positive immune cells occupying the tumor. Low expression of stromal CD8 and tumoral CD68 was associated with better overall survival. Overall survival did not differ significantly between patients with low or high PD-L1 expression. Conclusion: Increased numbers of CD8-positive cytotoxic T lymphocytes, CD68-positive macrophages, and PD-L1-positive tumor/immune cells were observed in MMR-deficient EC. BHLHE22 expression was associated with the PR regulatory and immune-related pathways.